THE ANALYSIS OF INDIVIDUAL’S BEHAVIORAL INTENTION AND USE BEHAVIOR IN USING OVO BASED ON UTAUT 2 - Lail, Fatimatul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
Cashless lifestyle has rapidly gained its popularity with the introduction of e-wallet as aninnovation form of e-money such as OVO to enhance an effective and efficient means oftransaction. However, the successful implementation of OVO as an e-wallet largely dependson the extent of how the customers are fully motivated to adopt it. The purpose of thisresearch is to explain the factors which influence the behavioral intention and use behavior toutilize OVO. The proposed model has factors from Unified Theory of Acceptance and Use ofTechnology 2 (UTAUT 2). This research applies an explanatory research and the data arecollected by employing survey method (questionnaires). The respondents comprise of 328undergraduate active students from accounting department in Faculty of Economics andBusiness, Brawijaya University. The research data and hypothesis are analyzed by usingStructural Equation Modeling (SEM) based on Partial Least Square (PLS). The researchfindings mainly indicate that behavioral intention to utilize mobile banking is significantlyand positively influenced by performance expectancy, hedonic motivation, and habit. It isequally important that behavioral intention also has a strong and positive effect towards usebehavior. In contrast, effort expectancy, social influence, and price value do not affect theuses’ behavioral intention to use OVO. Thus, it can be concluded that higher performanceexpectancy, hedonic motivation and habit, will highly affect the intention to use OVO, andhigher behavioral intention will highly impact the use behavior of using OVO. Keywords: E-money, E-wallet, Performance Expectancy, Effort Expectancy, SocialInfluence, Price Value, Hedonic Motivation, Behavioral Intention, Use behavior.